Az ipari parkok jellemző vonásai a Nyugat/Vest romániai régióban - Komarek, Levente (Közép-Európai Közlemények, 2010)
Both the category industrial park and the West/Vest Romanian region have relatively short past, still they have become important pillars in the development of industry and job creation by now. It is understandable then that a special attention is paid to the situation, development level, unused reserves and bottlenecks of the industrial parks of the region, and also to the possibilities to increase their capital absorption capacity. In launching the West/VestRomanian region on a more dynamic development path, an important tool can be a network of well-functioning modern industrial parks, flexibly adapting to the changing demands and acting as an innovative factor. The attraction of the respective industrial parks, the number of companies locating in them, the stability, the feeling and the development possibilities of the businesses in the parks, as well as the location decisions of the new or potential clients are influenced by several non-quantifiable, subjective elements, factors. The study introduces the industrial parks of the West/VestRomanian region, the spatial location of the industrial parks and the services that they offer.